APPLICATION OF "HAUL LOC" TECHNOLOGY FOR DUST SUPPRESSION OF INDUSTRIAL ROADS SURFACE - Долина, Олександр; Гацький, Анатолій (SWorldJournal, 2024)
The effectiveness of the use of the reagent "Haul loc" from the GRT company to control the level of dust partition on technological roads in comparison with the control area without the application of dust-binding substances was analyzed. The effectivenes